The Cardiovascular Keys to Air-Breathing and Permanent Land-Living in Vertebrates: the normal human embryonic aortic switch procedure produced by complete right-left asymmetry in the development of the subarterial conal free walls, and the evolution of the right ventricular sinus - Van Praagh, Richard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The subarterial conal free walls in Homo sapiens normally perform an embryonic aortic switch procedure by 38 to 45 days of age in utero. The right-sided subaortic conal free wall normally undergoes complete resorption. Simultaneously, the left-sided subpulmonary conal free wall grows and expands, elevating the pulmonary valve superiorly and anteriorly – above the developing right ventricle, away from the interventricular foramen. Resorption of the right-sided subaortic conal free wall permits the aortic valve to move posteriorly, inferiorly, and leftward – through the interventricular foramen to above the developing left ventricle. This asymmetric or opposite right-left development of the subarterial conal free walls results in normally related great arteries (solitus and in versus ). There is only one way of doing the embryonic aortic switch right (with solitus and in versus isomers), and many ways of doing it wrong. All of the conotruncal malformations have anomalies of right-left conal free wall asymmetry. Molecular genetic evidence suggests that malformations of right-left development may be caused by one or more mutations in the Nodal cascade. The heterotaxy syndromes, often misunderstood as malformations of bilateral symmetry (bilateral right-sidedness or bilateral left-sidedness), are also anomalies of right-left asymmetry. The other important evolutionary development was the appearance of the right ventricular sinus (inflow tract) beneath the proximal or apical part of the conus. The right ventricular sinus is the lung pump. Hence, a double circulation – systemic and pulmonary – evolved in fully terrestrial vertebrates. The cardiovascular system is the first system that must become functional in the human embryo to permit the rapid development of multicelled animals such as ourselves. Congenital heart disease is the commonest congenital malformation in live-born humans – almost 1% (0.8%). Most human congenital heart disease consists of anomalies of one or more of the four components that make up the right ventricle. Anomalies of the left ventricle are comparatively infrequent. In our phylum Chordata, the morphologically left ventricle is at least 500 million years old. By contrast, the morphologically right ventricle is only about 180 million years old, i.e., only about 36% as old as the left ventricle. We are still having trouble with our comparatively recent cardiovascular evolutionary adaptations to air-breathing and permanent land-living: the development of the right ventricular sinus and the embryonic aortic switch. These two cardiovascular evolutionary developments helped to make possible our long terrestrial prehistory, our history, our cultures, our science, our “everything”.